Association of breastfeeding, maternal anthropometry and body composition in women at 30 years of age - Lima,Natália Peixoto (2019)
This study aimed at assessing the association of breastfeeding with maternal body mass index (BMI), waist circumference, fat mass index, fat free mass index, android/gynoid fat ratio and bone mineral density. In 1982, the maternity hospitals in Pelotas, Rio Grande do Sul State, Brazil, were daily visited and all live births were identified and examined. These subjects underwent follow-up for several times. At 30 years of age, the participants were interviewed and examined. Parous women provided information on parity and duration of breastfeeding. Multiple linear regression was used in the multivariate analysis, controlling for genomic ancestry, family income, schooling and smoking at 2004-2005. After controlling for confounding factors, breastfeeding was inversely associated with BMI and fat mass index, whereas breastfeeding per live birth was negatively associated with BMI, waist circumference and fat mass index. Women who had had a child in the last 5 years and had breastfed, showed lower BMI (β = -2.12, 95%CI: -4.2; -0.1), waist circumference (β = -4.46, 95%CI: -8.3; -0.6) and fat mass index (β = -1.79, 95%CI: -3.3; -0.3), whereas no association was observed among those whose last childbirth was > 5 years, but the p-value for the tests of interaction were > 0.05. Our findings suggest that breastfeeding is associated with lower BMI and other adiposity measures, mostly in the first years after delivery. Besides that, it has no negative impact on bone mineral density.